SMS communication : a linguistic approach - Cougnon, Louise-Amélie; Fairon, Cédrick (Benjamins current topics ;, 2014)
Given the extensive use of LOL (Laughing Out Loud), MDR (Mort De Rire) and PTDR (PéTé De Rire) in French texting and the inclusion of lol in the Oxford English Dictionary in 2011 and in Le Petit Robert in 2013, this paper aims to study the functioning of these three initialisms. Considered mainly as interjections, I hypothesize that lol, mdr, and ptdr could work syntactically (through their non-integration in the syntactic clause and position) and semantically (through their semantic opacity and procedural meaning) as discou.